2013
DOI: 10.1002/zaac.201200497
|View full text |Cite
|
Sign up to set email alerts
|

Crystallography under External Electric Field

Abstract: Structural response of crystals to an applied external perturbation is important as a key for understanding microscopic origin of physical properties. Experimental investigation of structural response is a great challenge for modern structure analysis. We demonstrate how advanced X-ray diffraction techniques facilitate probing tiny (10 -4 Å) distortions of bond lengths under a permanent electric field. We also discuss details of the experimental procedure essential for reaching such precision. We ask whether t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
31
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 52 publications
1
31
0
Order By: Relevance
“…A formalism for analysis of diffraction data collected on electrically biased single crystals has been developed previously1 and used to determine field-induced changes of bond lengths in several piezoelectrics, including α-GaPO 4 2, LiNbO 3 3 and LiSO 4 ·H 2 O2. However, for many useful systems, large single crystals are unavailable and applications rely on more easily produced polycrystalline materials.…”
mentioning
confidence: 99%
“…A formalism for analysis of diffraction data collected on electrically biased single crystals has been developed previously1 and used to determine field-induced changes of bond lengths in several piezoelectrics, including α-GaPO 4 2, LiNbO 3 3 and LiSO 4 ·H 2 O2. However, for many useful systems, large single crystals are unavailable and applications rely on more easily produced polycrystalline materials.…”
mentioning
confidence: 99%
“…Piezoelectricity may be caused by 'intrinsic' phenomena, which are described in crystallographic terms such as atomic displacements, lattice parameters, and the type of space group and symmetry group (Gorfman et al, 2006(Gorfman et al, , 2013. However, the most important functional piezoelectrics are also ferroelectrics, and these classes of materials may exhibit phenomena on much longer length scales (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, in situ synchrotron X-ray diffraction combined with the application of an electric field during measurements has been used in recent years to provide useful and precise information beyond the usual applications for structural studies. [14][15][16][17] A good review on the time-resolved X-ray diffraction methods can be found in Ref. 18.…”
Section: Introductionmentioning
confidence: 99%